2012
DOI: 10.1007/s10956-012-9389-5
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Energy Science as Inquiry: Reflections on Professional Development as a Tool to Build Inquiry Teaching Skills for Middle and High School Teachers

Abstract: A hybrid (face-to-face and online) professional development (PD) course focused on energy science for middle and high school teachers (N = 47) was conducted using the teaching science as inquiry (TSI) framework. Data from the PD indicates that online opportunities enhanced participation and that the TSI structure improved teachers' inquiry implementation. Teachers found the TSI modes of inquiry easily accessible and effectively implemented them (modes correspond to the inquiry mechanisms of investigation, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 9 publications
0
13
0
6
Order By: Relevance
“…It further indicates that it would be practical to improve science teachers' subject knowledge of bioenergy so that they can teach it with high confidence to their students. This is also relevant as Seraphin et al [5] have suggested that when teachers have a strong scientific base in energy science, only then will they be able to identify and challenge students' misconceptions and help their learning process. The science teachers appeared to be positive towards receiving more information on bioenergy; therefore, it might be possible to encourage them to participate in content-based training courses where they become aware of bioenergy related topics, improve their subject knowledge, and enhance their capacity to teach such topics in schools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It further indicates that it would be practical to improve science teachers' subject knowledge of bioenergy so that they can teach it with high confidence to their students. This is also relevant as Seraphin et al [5] have suggested that when teachers have a strong scientific base in energy science, only then will they be able to identify and challenge students' misconceptions and help their learning process. The science teachers appeared to be positive towards receiving more information on bioenergy; therefore, it might be possible to encourage them to participate in content-based training courses where they become aware of bioenergy related topics, improve their subject knowledge, and enhance their capacity to teach such topics in schools.…”
Section: Discussionmentioning
confidence: 99%
“…In a broader sense, teachers can also play a key role to promote ESD in schools, as schools are the first level of formal education in our modern society. Chedid [4] also suggested that "teachers are the primary link for preparing students for the future energy related jobs" and Seraphin et al [5] emphasized that "teachers should have high levels of proficiency and confidence in their ability to teach energy science in schools". However, it has been found that insufficient teacher knowledge related to energy and environmental subjects is a limiting factor for the promotion of EE in schools [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modes of inquiry addressed in TSI (modified from DuncanSeraphin, Philippoff, Parisky, Degnan, & Papini Warren, 2012) …”
mentioning
confidence: 99%
“…In recent years however, it has been recognized that teachers may hold different levels of efficacy about different aspects of science teaching. For example, studies have focused on efficacy for chemistry teaching (Uzuntiryaki, 2008), teaching science by inquiry (Seraphin, Philippoff, Parisky, Degnan, & Warren, 2013), integrating Facebook into teaching (Blonder & Rap, 2017), teaching socioscientific issues (Kilinç et al, 2014), and integrating ICT into science (Annetta, Frazier, Folta, Holmes, Lamb, & Cheng, 2013).…”
Section: Measurements Of Specific Science Teaching Self-efficacy Beliefsmentioning
confidence: 99%